(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the research is to determine the factors that influence the scientific production of teachers in Peru. Approached from the positivist paradigm, quantitative approach and basic type, descriptive-explanatory, the sample made up of 215 university professors calculated with probabilistic sampling, was used in the questionnaire and the survey as an instrument and technique, respectively. Content and construct validity were performed, as well as the reliability of the instrument through Cronbach's alpha, Omega and Theta. The factors that influence scientific production are: institutional factor, personal factor and the stimulus factor. It is concluded that the predominant factor that influences scientific production is the stimulus and the predominant indicators are incentives, prizes, bonuses, knowledge and participation in research methodology courses, empowerment or individual capacities and the personal motivation of teachers in scientific production.